Molecular analysis of floral meristem identity genes in black pepper (Piper nigrum L.) - Hemanth (Department of Plant Biotechnology, College of Agriculture, 2014)
The present study entitled “Molecular Analysis of Floral Meristem Identity Genes in Black Pepper (Piper nigrum L.)” was conducted at the Department of Plant Biotechnology, College of Agriculture, Vellayani, during 2012-2014. The study envisaged isolation and sequencing of genes homologous to key floral meristem identity genes in black pepper (variety - Karimunda) and functional characterization of these genes by studying their expression patterns. Two floral meristem identity genes viz., FRUITFULL 1 (FUL1) and APETALA 1 (AP1) were chosen to identify in black pepper. Degenerate primers were designed for the above said genes based on the gene sequences from NCBI database (FUL1 and AP1 forward and reverse primers) which were used to isolate and identify the genes. Genomic DNA of black pepper was isolated using modified CTAB method and RNA was isolated using Trizol reagent method followed by synthesis of cDNA using AMV RT (Avian myeloblastosis virus reverse transcriptase). PCR (Polymerase chain reaction) with degenerate primers using DNA as template showed no amplification. When cDNA was used as a template for PCR no amplification was found with degenerate AP1 primers. However with FUL1 primers, two bands of size ~400bp and ~150bp were produced when cDNA of immature spikes were used as a template for PCR. These fragments were sequenced and analyzed, analysis of sequences showed that the bigger fragment i.e. ~400bp showed similarity to HSP90 (Heat shock protein 90) and the sequence of the smaller fragment which is around 152bp showed similarity to the floral meristem identity gene APETALA1 making it the first ever floral gene to be identified in the black pepper. The sequence of the bigger fragment was published in the NCBI database as the HSP90, partial mRNA sequence of black pepper [Accession number is KJ534563]. This is the first ever Heat shock protein gene to be identified, sequenced and published in black pepper. Specific primers were designed for qRT-PCR (Quantitative RT-PCR) to study the expression of the sequenced floral meristem identity gene, it was confirmed that this gene was expressed only in immature spikes of black pepper. Microscopy studies were carried out to see the changes occurring in different development stages of spikes from immature spike to complete spike with berries and also to correlate the expression of the identified floral meristem identity gene in the different tissues. This study helped to clearly identify the expression of the identified floral meristem identity gene, which is expressed in the immature stage of the spike.